Why lawyers internationalize and police transnationalize: disjointed criminal justice at the border of the state - Christensen, Mikkel Jarle (Crime, law and social change, 2022)
This article investigates the socio-genesis of two different types of criminal justice developed at the border of the state. At this border, the field of international criminal justice was differentiated from the field of transnational criminal justice. The article analyzes how elites of these two fields are characterized by distinct relations to the state that structure their ability to affect criminal justice outside of the national context. These professionals worked in parallel in national systems of justice where they accumulated distinct patterns of expertise and access to the state. On the basis of these socio-professional differences, law and police professionals helped define new criminal justice initiatives at the border of the state that deepened the division between them. The development of international criminal justice was dominated by professionals of law whereas transnational criminal justice was built primarily around police professionals. Societal responses to globalized crime are structured by this disjointed space of criminal justice in which legal and police professionals dominate distinct enforcement initiatives.